2007
DOI: 10.1104/pp.107.109538
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic and Expression Compendium of the ExpandedPEBPGene Family from Maize

Abstract: The phosphatidylethanolamine-binding proteins (PEBPs) represent an ancient protein family found across the biosphere. In animals they are known to act as kinase and serine protease inhibitors controlling cell growth and differentiation. In plants the most extensively studied PEBP genes, the Arabidopsis (Arabidopsis thaliana) FLOWERING LOCUS T (FT) and TERMINAL FLOWER1 (TFL1) genes, function, respectively, as a promoter and a repressor of the floral transition. Twenty-five maize (Zea mays) genes that encode PEB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
276
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(299 citation statements)
references
References 75 publications
17
276
1
Order By: Relevance
“…Thus, our findings challenge the prediction that downstream genes like FT are more likely to exhibit regulatory variation (Schwartz et al 2009). The redundancy afforded by a recent history of duplication, the novel derived expression domain of HaFT1, or multifarious selection acting on multiple pleiotropic effects may have uniquely fostered a selective sweep on a structural change in this case (Blackman et al 2010); however, given the expansion of FT/TFL1 homolog numbers observed in other species (Carmel-Goren et al 2003;Faure et al 2007;Nishikawa et al 2007;Danilevskaya et al 2008;Igasaki et al 2008;Mimida et al 2009), similar results may soon be observed in additional systems. FIGURE S1.-Sunflower COL homologs cluster with the CO-COL1-COL2 clade.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, our findings challenge the prediction that downstream genes like FT are more likely to exhibit regulatory variation (Schwartz et al 2009). The redundancy afforded by a recent history of duplication, the novel derived expression domain of HaFT1, or multifarious selection acting on multiple pleiotropic effects may have uniquely fostered a selective sweep on a structural change in this case (Blackman et al 2010); however, given the expansion of FT/TFL1 homolog numbers observed in other species (Carmel-Goren et al 2003;Faure et al 2007;Nishikawa et al 2007;Danilevskaya et al 2008;Igasaki et al 2008;Mimida et al 2009), similar results may soon be observed in additional systems. FIGURE S1.-Sunflower COL homologs cluster with the CO-COL1-COL2 clade.…”
Section: Discussionmentioning
confidence: 79%
“…The other gene, c2588, belongs to the same gene family as INDETERMINATE1/EARLY HEADING DATE2 (ID1/Ehd2), a zinc-finger transcription factor and upstream regulator of FT homologs in monocots (Colasanti et al 1998;Matsubara et al 2008). While TFL1 homologs regulate flowering and other photoperiodic responses across diverse plants (Bradley et al 1997;Pnueli et al 1998;Nakagawa et al 2002;Foucher et al 2003;Guo et al 2006;Danilevskaya et al 2008;Ruonala et al 2008;Mimida et al 2009), the function of ID1/Ehd2 homologs in flowering may be monocot-specific. No direct ID1/Ehd2 ortholog exists in the A. thaliana genome, and phylogenetic analyses indicate the INDETERMINATE gene family independently diversified in the monocot and eudicot lineages (Colasanti et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…S1). Previous work defined two groups of FTlike proteins, I and II 32 , and our work suggests that both these groups can be further divided to make four subgroups: FT-like IA, IB, IIA and IIB (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…1a, proteins marked with asterisk). AcFT4 is positioned within subgroup IIA that also contains the FT-like proteins associated with the flowering of maize 32 (ZmZCN8) and barley 34,35 (HvFT3). AcFT3, AcFT5 and AcFT6 proteins are located in FT-like subgroup IB and a role has not been established for any of the proteins within this subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the maize gene zcn15 was found within a divergent region on a different area of chromosome 6 that contains a total of five annotated genes. Danilevskaya et al (2008) report that this is among the most favorable candidates for function as a promoter of the floral transition. Additional research is needed to determine whether the genes and regions putatively subjected to selection are directly involved in meristem function resulting in increased number of ears per plant in this population.…”
Section: Discussionmentioning
confidence: 99%